A low-blank two-column chromatography separation strategy based on a KMnO4 oxidizing reagent for Cr isotope determination in micro-silicate samples by thermal ionization mass spectrometry - Li, C.; Feng, L.; Wang, Xuan-Ce; Wilde, Simon; Chu, Z.; Guo, J. (Royal Society of Chemistry, 2017)
© 2017 The Royal Society of Chemistry. This study has led to a new technique for the separation of Cr from small silicate samples (0.3-2 mg) and determination of stable Cr isotopes in silicates by double spike thermal ionization mass spectrometry (DS-TIMS). Based on our recent two-step exchange resin scheme (Li et al., JAAS, 2016, 31, 2375), we further significantly reduced the procedural blank and improved Cr recovery (94.7-97.5%) from a range of complex silicate rocks varying in composition from andesite to ultra-mafic, and carbonates as well. The key improvement is that KMnO 4 was employed to replace conventional (NH 4 ) 2 S 2 O 8 as the oxidizing reagent, which reduces the procedural blank from 1-20 ng in previous studies to 0.15 ± 0.04 ng (n = 8). In addition, the inhibition effect on the Cr signal caused by residual SO 4 2- in the Cr fraction using the conventional method has been completely eliminated during TIMS measurements. This permits the high precision determination of Cr isotopic ratios from geological samples as small as ∼46 ng. This chemical procedure was verified using a variety of silicate rocks in the size range of 0.3-2 mg. A series of analyses demonstrated that it is possible to attain internal precisions (2 SE) of ±0.03 to 0.06‰. Replicate digestions and analyses of basalt standard BIR-1 with a sample size of 0.3 mg (δ 53 Cr = -0.158 ± 0.052‰, 2 SD) demonstrated that good intermediate precision is obtainable for extremely small silicate samples.